Ameliorative effect of polydatin and polydatin-loaded chitosan nanoparticles against diabetes-induced pulmonary disorders in rats - Fatma Mostafa (Journal of Taibah University for Science, 2021)
The current study aims to evaluate the ameliorative effect of polydatin-loaded-chitosan nanoparticles (PD-CSNPs), polydatin (PD), and metformin on Diabetes-induced pulmonary disorders. After induction of diabetes, rats are classified into five groups, diabetic control and diabetic rats treated daily for four weeks with; PD, PD-CSNPs, chitosan-nanoparticles and metformin. Rats treated with PD and PD-CSNPs showed a reduction in glycosylated-haemoglobin % and lipid peroxidation level, increased activities of superoxide peroxidase, superoxide dismutase and catalase, and glutathione content in treated diabetic rats lung. Furthermore, PD-CSNPs, PD and MET decreased tumour necrosis factor-alpha and nuclear factor-kappa-β and upregulated nuclear factor erythroid 2-related factor-2 and haem oxygenase-1. Histological and ultrastructural examinations revealed their ameliorative effect via reducing the bronchiolar and alveolar fibrosis, thickening of the interalveolar septum, and inflammatory cell infiltration. In conclusion, PD-CSNPs was more effective than MET and PD in improvement the diabetes-induced pulmonary disorders through its antioxidant, anti-inflammatory, and prolonged-release properties.